2021
DOI: 10.24952/tijaroh.v7i1.3084
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Wealth Management During the Covid-19 Pandemic

Abstract: The coronavirus disease (COVID-19) pandemic has severe health effects and serious implications for economic. This research is a conceptual article that describes concepts and principles of Islamic wealth management (IWM), Islamic financial planning practice during Covid-19 pandemic, and Islamic social finance for reducing the pandemic effect. There are five stages in IWM that is wealth accumulation, wealth consumption, wealth purification, wealth distribution, and wealth protection. Wealth distribution such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Throughout the Covid-19 pandemic, Islamic social finance is essential in reducing the economic and social impact which in Islamic wealth management is known as the wealth distribution (Cahyani et al, 2021). Islamic social finance, which consists of zakat, waqf, and Islamic microfinance institutions, has good potential to overcome poverty (Umar et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Throughout the Covid-19 pandemic, Islamic social finance is essential in reducing the economic and social impact which in Islamic wealth management is known as the wealth distribution (Cahyani et al, 2021). Islamic social finance, which consists of zakat, waqf, and Islamic microfinance institutions, has good potential to overcome poverty (Umar et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On this topic, not much research has been found. Among the relevant research is Cahyani et al (2021) discussing IWM during the Covid-19 pandemic. Based on his research it was found that in IWM, there are five stages of planning namely wealth accumulation, wealth consumption, wealth purification, wealth distribution, and wealth protection.…”
Section: Islamic Wealth Management (Iwm) During Pandemicmentioning
confidence: 99%